2019
DOI: 10.3389/fimmu.2019.00926
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Is Lethal to Flavobacterium psychrophilum Through Either Direct Membrane Permeabilization or Indirectly, by Priming the Immune Response in Rainbow Trout Macrophages

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a multifunctional neuropeptide that is widely distributed in mammals and is capable of performing roles as a neurotransmitter, neuromodulator, and vasodilator. This polypeptide belongs to the glucagon/secretin superfamily, of which some members have been shown to act as antimicrobial peptides in both mammalian and aquatic organisms. In teleosts, PACAP has been demonstrated to have direct antimicrobial activity against several aquatic pathogens, yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 80 publications
(88 reference statements)
1
11
0
Order By: Relevance
“…Further, the PACAP specific receptor adcyap1r11 (or pac1 ) was expressed in mature neuron clusters, while VIP receptors ( vipr1a , vipr1b , and vipr2 ), which PACAP is also a ligand for, were not detected in our transcriptomes (Figure 4E). Because PACAP-38 has been shown to be antimicrobial in both teleost and mammals (Lee et al, 2021; Semple et al, 2019) and to regulate feeding behavior in fish (Lugo et al, 2010) but not implicated in antiviral immunity we decided to investigate further this observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the PACAP specific receptor adcyap1r11 (or pac1 ) was expressed in mature neuron clusters, while VIP receptors ( vipr1a , vipr1b , and vipr2 ), which PACAP is also a ligand for, were not detected in our transcriptomes (Figure 4E). Because PACAP-38 has been shown to be antimicrobial in both teleost and mammals (Lee et al, 2021; Semple et al, 2019) and to regulate feeding behavior in fish (Lugo et al, 2010) but not implicated in antiviral immunity we decided to investigate further this observation.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of PACAP-38 sequences from D. rerio (NP_001259010.1:96-133), Homo sapiens mature PACAP-38 peptide (NP_001093203.1:132-169), and C. gariepinus from (Semple et al, 2019). Percent identity is compared to D. rerio .…”
Section: Supplemental Figurementioning
confidence: 99%
“…An example of this has been noted with pituitary adenylate-cyclase activating polypeptide (PACAP). When PACAP was administered in the presence of a bacterial pathogen, the AMP significantly enhanced the stimulation of proinflammatory transcripts [ 301 ]. When used alone, PACAP was able to significantly stimulate proinflammatory transcripts of rainbow trout immune cells, indicating that this peptide has an immunostimulatory activity similar to other studied mammalian AMPs [ 302 , 303 , 304 ].…”
Section: Current Methods Of Bacterial Disease Prevention In Aquacumentioning
confidence: 99%
“…PACAP is known to interact with the immune system (14,15) and modulate T helper type 1 (TH1)/TH2 cytokine production (3). Important previous work on structure activity relationships (SAR) of PACAP have also shown that it possess antimicrobial activity in vitro against a range of organisms (16)(17)(18), as well as anti-cancer activity against tumor cell lines. (Interestingly, our use of an SVM classifier that can scan different fragments of the same peptide allows us to identify antimicrobial activity in previously identified metabolites of PACAP as well* ( 19)).…”
Section: Significancementioning
confidence: 99%